Iron Ore Dust Control System at the San Nicolás-Marcona Benefit Concession Crushing Plant - Yabar Baños, Carlos (2020)
The objective of this applied research is to demonstrate the decrease in environmental pollution and occupational exposure by systematizing the iron ore dust control process at the San Nicolás benefit concession crushing plant of mining company Shougang Hierro Perú S. A. A. The causal relationship between environmental pollution and occupational exposure was established via the measurement of particulate matter. Perception of environmental pollution reduction was measured using a quantitative approach in a sample of 15 workers and data processing by means of descriptive and inferential statistical methods. The results show that the average level of influence of the iron ore dust control system is significant, at a confidence level of 95% and significance level of 5%. Therefore, the system efficiently reduces air pollutant values. Prior to implementation, the air pollutant value was 500 µg/m3, above the maximum permissible limit established in the current environmental quality standards; the occupational exposure to respirable dust particles was 3.2 mg/m3, and inhalable dust particles values, 13 mg/m3. After conducting environmental and occupational monitoring, air pollutant values of less than 220 µg/m3 were obtained, and occupational exposure to respirable dust particles and inhalable dust was reduced to 2.2 mg/m3 and 9.2 mg/m3, respectively, at the San Nicolás benefit concession crushing plant. It is concluded that the dust control system efficiently minimizes iron ore dust in the mentioned plant.